Barbie. Video game hero [videorecording (Blu-Ray + DVD)] - Bargiel, Nina G.; Skelly, Jennifer (Screenwriter); Kneubuhl, Rebecca (Universal Pictures Home Entertainment, 2017)
When Barbie is magically pulled into her favorite video game, she must rely on her amazing gaming skills and out-of-the-box thinking to save her team and beat the game.